Tampilan Kadar Asam Lemak Omega-3 dan Kolesterol Telur Ayam Konsumsi yang Diberi Ransum Mengandung Limbah Minyak Ikan Lemuru (Sardinella longiceps) - Joko Riyanto (Universitas Sebelas Maret, 2006)
The experiment was conducted to find of the effects of using sardine oil in rations on the performance of laying hens and quality eggs, especially the omega-3 fatty acids content in the chicken egg. There were four group of in this experiment: L0 (commercial feed) as control treatment, L1 (L0+5% sardine oil), L2 (L0+10% sardine oil) and L3 (L0+15% sardine oil). Data analyzed Completely Randomized Design (CDR) and each group consisted 24 quails. Results of this research showed that there are has a significant (P<0,05) effects on laying hens performance productions. The used of sardine oil in rations significantly influenced the omega-3 fatty acids and cholesterol content (P<0,05). The omega-3 fatty acid content on the egg consumption from the used of sardine oil in rations was highly (P<0,05) and the cholesterol content lower (P<0,05) than not the used of sardine oil in rations. The result showed that used of sardine oil in rations made the performance of laying hens better than the used of control rations. The increasing of sardine oils usage in rations to increased the omega-3 fatty acids content and to decrease of cholesterol content in the chicken egg. It was concluded that using sardine oil in the rations gave effect on the good performance of laying hens.